FIGHTING THE DISINFODEMIC: FACT- CHECKING MANAGEMENT OF HOAX COVID-19 IN INDONESIA - Dasrun Hidayat; Acep Rohendi; Deri Hanafy D; Maylanny Christin; Nur'aeni Nur'aeni (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
Indonesia was currently fighting disinfodemic COVID-19. During this situation, several hoaxes related to COVID-19 were circulating. Of course, the hoax news makes people even more worried and afraid. One way to prove the facts in that news is through a fact-checking system. This system is intended to check facts and verify information so that the truth can be identified. Fact-checking needs to be known by the public to suppress the spread of hoax news, especially related to the circulation of COVID-19 in Indonesia. Based on this phenomenon, the purpose of this study is to determine the informants’ experience related to the fact-checking process. The study informant referred to Mafindo, an internationally licensed fact-checking agency. To answer the objective of the research, the researcher used an ethnographic study of public relations with a qualitative approach. The ethnographic study of public relations focuses on examining communication activity planning using analysis units of Insight, Strategic Program, Program Implementation, Action, and Reputation or the IPPAR Model. The results of this study indicate that the Mafindo fact checker interprets the fact-checking for COVID-19 news as important, to reduce public concerns. The lack of reference sources to be used as data and evidence of hoax news becomes a challenge when doing fact-checking. The fact-checking phases include data collection, sorting, analyzing, and checking the results before publishing them to the public. The discussion is an effort to maintain the credibility of the results, image, and reputation of the fact-checker institution.